2008
DOI: 10.2151/jmsj.86.935
|View full text |Cite
|
Sign up to set email alerts
|

Transportation of Water Vapor into the Tibetan Plateau in the Case of a Passing Synoptic-Scale Trough

Abstract: The passing of a synoptic trough is expected to contribute strongly to water vapor (WV) transport processes from the Indian Ocean to the Tibetan Plateau (TP) during the monsoon season. However, the pathway of the WV into the plateau associated with passing a trough and its contribution to the WV budget over the TP are not clear. In this study, the processes of WV transport in the case of a passing trough in 1998 were analyzed using GAME reanalysis data and the numerical model, focusing especially on the WV tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 44 publications
3
30
0
Order By: Relevance
“…The role of intraseasonal variability, synoptic-scale system activities and diurnal variation in the atmospheric heat source and moisture over the TP (Sugimoto et al, 2008;Fujinami and Yasunari, 2004) will be considered in a future study on the warm-moist air transport up to the plateau. It should be emphasized that considering the quality of reanalysis data over and around the TP, a comparison between NCEP/NCAR and some other reanalysis data sets such as JRA-25, ERA-Interim, or MERRA is necessary in further work.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The role of intraseasonal variability, synoptic-scale system activities and diurnal variation in the atmospheric heat source and moisture over the TP (Sugimoto et al, 2008;Fujinami and Yasunari, 2004) will be considered in a future study on the warm-moist air transport up to the plateau. It should be emphasized that considering the quality of reanalysis data over and around the TP, a comparison between NCEP/NCAR and some other reanalysis data sets such as JRA-25, ERA-Interim, or MERRA is necessary in further work.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Cloud area A developed with a stagnant trough in the south of the plateau. Sugimoto et al [2008] showed a similar type of cloud development in Figure 5 of their paper when the water vapor was favorable for intrusion into the southeastern parts of the TP during the monsoon season. Cloud area B indicates the border between the Indian monsoon air mass and the dry midlatitude air mass as explained in section 4.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…Recently, coupling of the diurnal mode of precipitation system with a traveling synoptic scale trough has been given attention around the TP. For instance, diurnal circulation over the Himalayas could effectively pump up and converge the water vapor into the southeastern TP when a trough existed in the south of the TP during an Indian monsoon break phase [ Sugimoto et al , 2008]; moreover, a midlatitude trough enhanced nocturnal precipitation in the central TP, which would control the successive morning soil moisture condition [ Ueno et al , 2009]. As a traveling trough is the dynamic source for lee cyclogenesis and provides baroclinic instability in the east of the TP, the functions of a synoptic environment accompanied by passing midlatitude waves to the timing of MCS genesis need to be examined case‐by‐case, together with recent satellite observation data and numerical simulation techniques with finer grids.…”
Section: Introductionmentioning
confidence: 99%
“…The transport of moisture to the TP is crucial for a sustainable water supply in the downstream regions like the Yellow and Yangtze river valleys (Zhang et al, 2013). Moisture transport in and to the TP is influenced by mesoscale features (Sugimoto et al, 2008), but it is also driven by large-scale atmospheric circulation, most notably the monsoon systems (Webster et al, 1998) and the mid-latitude westerlies (Schiemann et al, 2009). The unique topography of the TP, with its large extent and an average altitude of more than 4000 m makes it of particular interest because of its interaction with large-scale circulation.…”
Section: Introductionmentioning
confidence: 99%